LEVEL OF COMMUNITY PARTICIPATION AT COMMUNITY-BASED DRINKING WATER SUPPLY IN KEBONAGUNG VILLAGE, PADANGAN SUBDISTRICT - Hidayati, Nurin Nikmah; Wicaksono, Agus Dwi; Hariyani, Septiana (Journal of Environmental Engineering and Sustainable Technology, 2024)
The Community-Based Water Supply and Sanitation Program (PAMSIMAS) is one of the government's concrete actions to meet water needs in the community. However, implementing the PAMSIMAS program in Kebonagung Village needs more community involvement.  Therefore, this study is conducted to identify the level of community participation using frequency distribution calculations based on Arnstein's participation ladder. Data collection was conducted through a primary survey with 41 respondents using a simple random sampling method, using random respondents who would be used as research samples. The results showed that the level of participation in the PAMSIMAS program in Kebonagung Village was on the fourth ladder of participation, namely consultation with classification into tokenism, which means that the community participates in obtaining information and has the opportunity to argue for decision improvement but is often not accommodated or ignored. It is necessary to increase community participation by paying more attention to community needs so that the sustainability of the PAMSIMAS program continues.